Finnish Employees and their Adaptation to International and Local-style Organizational Cultures in South Korea - Lepistö, Maria (My University, 2026)
Nature of labor markets is changing all over the world. People, capital, goods, and services move faster across borders than ever before. Interactions between companies and nations happen more frequently due to globalization and rise of multinational organizations. While movement of labor increases and companies move their factories abroad, understanding possible cultural differences and training employees to work in culturally different working environments is needed to build successful co-operations. National culture can influence many aspects like preferred organizational structures and job conditions, which will further affect employees’ satisfaction and adaptation into workplaces. Currently, there is only a handful of studies researching the cultural differences between Nordic and East Asian countries, and none researching Finnish employees in Korean workplaces. Moreover, current studies lack focus on individual experiences when studying adaptation into organizations in other countries. In this research, I focused on informants’ subjective experiences on how Finnish and Korean cultures might affect Finnish employees’ adaptation to workplaces in Korea. Most important results from the interviews were as follows. Upper management faced challenges especially in relation to Korean employees’ kinship and third-party relations that were hard for them to manage as foreigners. However, it was rather easy for upper management to come into the company as they automatically obtained their position and power. Employees in subsidiaries of European companies seemed to adapt rather easily as they did not have to adapt to all host country’s cultural or organizational practices since they were under home company’s work legislation and practices. Finally, Finnish employees in irregular jobs and Korean-style companies seemed to face most everyday challenges related to hierarchy, communication, and work-life balance. Especially short yearly holidays, and strict rules and lack of autonomy regarding work tasks and communications, was challenging for Finnish employees. This research can benefit Nordic companies and subsidiaries in East Asia by increasing their productivity and expertise pool through hiring foreign workers who adapt and work efficiently in companies abroad. Furthermore, this information can be used to help future employees from Finland or other Nordic countries to gain some knowledge and perspectives about Korean workplace culture before their placement. To answer my research questions, I used qualitative methods to collect and analyze my data. I conducted interviews on five Finnish informants who had experience working in Korea. Further, I used a thematic analysis to identify and analyze specific patterns and themes within the obtained interview data.
Keywords: Interculturalism; adaptation; organizational culture; foreign employee; South Korea; Finland; Nordic countries